Simvastatin protects auditory hair cells from gentamicin-induced toxicity and activates Akt signaling in vitro - Brand Yves; Setz Cristian; Levano Soledad; Listyo Alwin; Chavez Eduardo; Pak Kwang; Sung Michael; Radojevic Vesna; Ryan Allen F; Bodmer Daniel (BMC Neuroscience, 2011)
Abstract Background Inhibitors of 3-hydroxy-3-methylglutaryl-coenzyme A reductase, known as statins, are commonly used as cholesterol-lowering drugs. During the past decade, evidence has emerged that statins also have neuroprotective effects. Research in the retina has shown that simvastatin, a commonly used statin, increases Akt phosphorylation in vivo, indicating that the PI3K/Akt pathway contributes to the protective effects achieved. While research about neuroprotective effects have been conducted in several systems, the effects of statins on the inner ear are largely unknown. Results We evaluated whether the 3-hydroxy-3-methylglutaryl-coenzyme A reductase is present within the rat cochlea and whether simvastatin is able to protect auditory hair cells from gentamicin-induced apoptotic cell death in a in vitro mouse model. Furthermore, we evaluated whether simvastatin increases Akt phosphorylation in the organ of Corti. We detected 3-hydroxy-3-methylglutaryl-coenzyme A reductase mRNA in organ of Corti, spiral ganglion, and stria vascularis by reverse transcriptase-polymerase chain reaction (RT-PCR). Moreover, we observed a dose-dependent and significant reduction of hair cell loss in organs of Corti treated with simvastatin in addition to gentamicin, as compared to samples treated with gentamicin alone. The protective effect of simvastatin was reversed by addition of mevalonate, a downstream metabolite blocked by simvastatin, demonstrating the specificity of protection. Finally, Western blotting showed an increase in organ of Corti Akt phosphorylation after simvastatin treatment in vitro. Conclusion These results suggest a neuroprotective effect of statins in the inner ear, mediated by reduced 3-hydroxy-3-methylglutaryl-coenzyme A reductase metabolism and Akt activation.